Carbon Nanomaterials Based Electrochemical Sensors/Biosensors for the Sensitive Detection of Pharmaceutical and Biological Compounds - Bal-Ram Adhikari; Maduraiveeran Govindhan; Aicheng Chen (Sensors, 2015)
Electrochemical sensors and biosensors have attracted considerable attention for the sensitive detection of a variety of biological and pharmaceutical compounds. Since the discovery of carbon-based nanomaterials, including carbon nanotubes, C60 and graphene, they have garnered tremendous interest for their potential in the design of high-performance electrochemical sensor platforms due to their exceptional thermal, mechanical, electronic, and catalytic properties. Carbon nanomaterial-based electrochemical sensors have been employed for the detection of various analytes with rapid electron transfer kinetics. This feature article focuses on the recent design and use of carbon nanomaterials, primarily single-walled carbon nanotubes (SWCNTs), reduced graphene oxide (rGO), SWCNTs-rGO, Au nanoparticle-rGO nanocomposites, and buckypaper as sensing materials for the electrochemical detection of some representative biological and pharmaceutical compounds such as methylglyoxal, acetaminophen, valacyclovir, β-nicotinamide adenine dinucleotide hydrate (NADH), and glucose. Furthermore, the electrochemical performance of SWCNTs, rGO, and SWCNT-rGO for the detection of acetaminophen and valacyclovir was comparatively studied, revealing that SWCNT-rGO nanocomposites possess excellent electrocatalytic activity in comparison to individual SWCNT and rGO platforms. The sensitive, reliable and rapid analysis of critical disease biomarkers and globally emerging pharmaceutical compounds at carbon nanomaterials based electrochemical sensor platforms may enable an extensive range of applications in preemptive medical diagnostics.